A rare case of Ellis-van Creveld syndrome with primary immunodeficiency with recurrent and persistent pneumonia (Northern International Medical College Journal, 2024)
Abstract not availableNorthern International Medical College Journal Vol. 13 No. 1-2 July 2021-January 2022, Page 594-597